2017
DOI: 10.1590/0103-8478cr20170279
|View full text |Cite
|
Sign up to set email alerts
|

Soil solution and plant nitrogen on irrigated rice under controlled release nitrogen fertilizers

Abstract: A study was conducted to evaluate the solubilization and nitrogen (N) use efficiency (NUE) of controlled release nitrogen fertilizers in irrigated rice, compared to urea. It was developed under semi-controlled conditions, including five treatments: Control, Splitted Urea (pre-sowing and topdressing), Pre-sowing urea, and Polymer Coated Urea (PCU) with 60-day and 90-day release. PCUs did not maintain high NH4 + and NO3 - levels in solution over a longer period than urea. NUE of PCUs was similar to uncoated urea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
(12 reference statements)
1
5
0
Order By: Relevance
“…The pH of the soil may change depending on the dose and fertilizer type used, soil characteristics and established crop (Veçozzi et al, 2018). In this study, the effect of the fertilizer type was only confirmed during 20 days, specifically, before the first cut of the brachiaria grass.…”
Section: Active Acidity Electrical Conductivity and Macronutrient Con...mentioning
confidence: 59%
“…The pH of the soil may change depending on the dose and fertilizer type used, soil characteristics and established crop (Veçozzi et al, 2018). In this study, the effect of the fertilizer type was only confirmed during 20 days, specifically, before the first cut of the brachiaria grass.…”
Section: Active Acidity Electrical Conductivity and Macronutrient Con...mentioning
confidence: 59%
“…No studies testing coated urea in the cultivation of cactaceae were found. However, Veçozzi et al (2018) evaluated the solubilization and NUE of nitrogen fertilizers of controlled release in irrigated rice and it was found that the NUE of the urea coated by polymers was similar to the conventional urea, not increasing the release time of the nutrient in this cultivation system.…”
Section: Discussionmentioning
confidence: 98%
“…The current study indicates that the coated urea, in yellow latosol with medium clay content, under these climatic conditions had low efficiency in the cultivation of cactus pear when compared to the conventional urea. It is important to highlight that the use of coated urea must be economically viable, and it is necessary that the increase in efficiency causes productivity gains that compensate the investment in a higher cost product, allowing the substitution of conventional sources (Veçozzi et al, 2018). The responses of the agronomic parameters of cactus pear variety Doce were proportional to the increase in the level of N, with the best level being 240 kg N/ha.…”
Section: Discussionmentioning
confidence: 99%
“…Pedrinho et al (2015) working with rapid cycle crop, as the lettuce, and with slow release and traditional urea, found no differences in productivity among the studied sources. Veçozzi et al (2018) using N sources with urea and urea coated with polymers, in the irrigated rice crop, found no effect among the sources.…”
Section: Introductionmentioning
confidence: 94%